'So Complete Was Our Victory! So Complete Their Ruin!': An analysis of the battle of Çeşme, 1770. Issue 3 (3rd July 2017) - MacDougall, Philip
Abstract : This article presents an analysis of why a technically advanced Ottoman fleet of overwhelming numerical superiority operating in its home waters should have been decisively defeated by a Russian fleet operating in totally unfamiliar waters and hampered by a divided command structure, with no truly safe harbour to fall back on and with ships manned by crews completely untried and untested in a combat situation. In this assessment of the battle of Çeşme fought in July 1770, attention will be given to the organizational failings of the Ottoman navy combined with a general inability of those who commanded naval affairs to recognize the importance of sea power and how it could be used to most effect. It is also demonstrated that while lessons were learnt, the pace of subsequent reforms, especially those required to correct crucial administrative and leadership shortcomings, was painfully slow and not finally completed until the later years of the following century. The outcome was a series of further naval defeats and a resulting loss of territory that led to the navy starved of adequate finance, a situation from which it never recovered.